EFFECT OF SUSTAINABILITY DISCLOSURE PERFORMANCE INDICATORS ON PROFIT MANAGEMENT WITH COMPANY SIZE AS A CONTROL VARIABLE - Hanifah, Risti Ulfi; Wijayanti, Provita (Master of Management, Faculty of Economics and Business, Diponegoro University, 2023)
Sustainability disclosure is a disclosure that can communicate to all stakeholders about economic, environmental, and social performance in realizing sustainable development goals. Stakeholder demands to meet the need for more transparent and accountable disclosure by organizations and pressures companies to collect, process, manage, and publish sustainability information. This will be reflected in a more accountable and transparent management of the cost of capital, which can affect the level of revenue management in the company's historical reports. The interesting question is the disclosure of sustainability with the level of profit management in the company over the company's more transparent revenue and the absence of profit manipulation practices carried out by management. The concept of discretionary accruals gives the understanding that management can manipulate accrual income and is usually used to achieve the desired income.This study aims to test empirical evidence regarding the influence of sustainability report indicators on profit management through discretionary accruals with company size as a control variable carried out on companies listed on the Indonesia Securities Exchange in 2018-2021. The samples in this study used non-financial companies with a total sample of 82 selected companies with purposive sampling techniques. This study used Partial Least Squares (PLS) based on variance as a measuring instrument. The data obtained were analyzed using the WarpPLS 5.0 application.Based on the findings, it shows the importance of the role of sustainability reports in terms of each aspect in their influence on profit management. It was concluded that the sustainability report consisting of economic and social aspects has a positive effect on profit management, while the environmental aspect negatively affects profit management, profit management negatively affects the size of the company as a control variable.